Phytotoxic and Enzymatic Study of Philodendron meridionale on seeds of Lactuca sativa L. (Research, Society and Development, 2021)
In an effort to identify novel biopesticides, the present study aimed to assess the effects of Philodendron meridionale (Buturi & Sakur) stem and leaf ketonic and ethanolic extracts (SKE, SEE, LKE, and LEE, respectively) on the germination, growth, root respiration, and enzymatic activities of Lactuca sativa L. seeds, and to measure the associated saponins, phenolics, and flavonoids that may possess herbicidal, pharmaceutical, or pesticidal activities. The extracts were obtained using a modified Soxhlet apparatus and methanolic extracts of 0.1, 0.25, 0.5, 0.75 and 1.0 mg.mL-1 were tested, with water and methanol as a control. The presence of saponins and the concentration of phenolic compounds were determined. Allelopathic activity was evaluated in tests of germination, growth, cellular respiration and enzymatic activity. The presence of saponins and the concentration of phenolic compounds equivalent to 225.12 for LKE, 240.45 for LEE, 193.28 for SKE, and 265.14 for SEE (mg·g-1.gallic acid), and flavonoids 52.74 for LKE, 54.31 for LEE, 72.74 for SKE, and 67.21 for SEE (mg.g-1.quercetin) were determined. The allelopathy of the P. meridionale extracts against L. sativa was confirmed through negative effects on L. sativa seed germination, radical growth and morphology, dry mass, and the concentrations of α-amylase (EC 3.2.1.1), ascorbate peroxidase (EC 1.11.1.11), catalase (EC 1.11.1.6), and polyphenol oxidase (EC 1.10.3.1). It was likely that the allelopathic action of the P. meridionale extracts was related to its effects on the membrane permeability and oxidative stress of the treated L. sativa seeds. The P. meridionale extracts contained saponins, calcium oxalate crystals, and flavonoids, including phenolic compounds, which are known allelochemicals with herbicidal activities.